Pengaruh Brand Awareness Terhadap Electronic Word Of Mouth Yang Berimbas Pada Keputusan Menginap - Wijaya, Gede Crisna; Megantari, Ni Wayan Cahya Tiara (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Brand Awareness on Electronic Word of Mouth which has an impact on the decision to stay at Prama Sanur Beach. This research was conducted at the Prama Sanur Beach Hotel which holds the title as one of the 5 star hotels in Bali. The population of this study is all guests who have stayed overnight registered in 2019-2021 as many as 285,933 people. In this study using quantitative methods. Sampling in this study using purposive sampling technique. Determination of sample size using the slovin formula with a sample size of 100 people. The data analysis technique used is path analysis. The results of this study indicate that partially the Brand Awareness variable has a positive and significant effect of 0.632 on the Electronic Word of Mouth. Electronic Word of Mouth has a positive and significant effect of 0.434 on the decision to stay. Brand Awareness has a positive and significant effect of 0.487 on the decision to stay. Brand Awareness has a positive and significant effect of 0.274 on the decision to stay through the Electronic Word of Mouth.